Greenfield's surgery scientific principles and practice - Greenfield, Lazar J. 1934-; Mulholland, Michael W. (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2011)
"The Fifth Edition of Greenfield's Surgery has been thoroughly revised, updated, and refocused to conform to changes in surgical education and practice. Reflecting the increasingly clinical emphasis of residency programs, this edition features expanded coverage of clinical material and increased use of clinical algorithms. Key Points open each chapter, and icons in the text indicate where Key Points are fully discussed. Many of the black-and-white images from the previous edition have been replaced by full-color images"--Provided by publisher